Mnenje slovenskih kirurgov o uporabi štiritočkovnih ortoz za koleno pri poškodbah križnih vezi - Macura, Marko (Rehabilitacija (Ljubljana), 2019)
Background: Anterior cruciate ligament (ACL) injuries are increasing in incidence in the last decades due to the modern lifestyle. ACL stabilizes the knee in the antero-posterior direction but provides stability in rotational/pivoting movements as well. The knee can be stabilised by surgical ACL reconstruction or by applying a four-point knee brace (4PB). In addition, the brace can also be used for postoperative protection of the reconstructed ACL. However, present studies provide no hard evidence regarding efficiency of the brace in postoperative ACL graft protection. Methods: A mini survey was conducted among ACL surgeons in Slovenia, asking about the surgeons' practice on using 4PB in ACL injuries. Questions were asked about using 4PB before surgery, instead of surgery and possible postoperative use for ACL-graft protection. Results: 25 ACL surgeons were contacted; 23 surgeons responded. Only one surgeon advised postoperative use of 4PB occasionally when he felt that the patient would not comply with postoperative regimen. All of the surgeons who responded use 4PB regularly in multidirectional knee instability due to multiligament injury. Conclusions: Slovenian ACL surgeons regularly prescribe 4PB in multiligament knee injuries, before and after surgery. In isolated ACL injuries, 4PB is used in conservative treatment if stability is not achieved even after proper rehabilitation. 4PB is not regularly used in postoperative period for isolated ACL reconstruction.
Keywords: anterior cruciate ligament; four-point brace; knee instability; nestabilnost kolena; Orthotic Devices; postoperative knee protection; sprednja križna vez; štiritočkovna opornica; zaščita kolena po operaciji